WORK SHEET FOR FUNDS STATEMENT PROBLEMS. - Gregory, Robert H.; Wallace, Edward L. (The Accounting Review, 1953)
Abstract An examination of American accounting literature indicates that five methods have been used to solve accounting problems requiring the preparation of source and application of funds statements. These methods are: (1) comparative balance sheets, (2) working sheets, (3) "T" accounts, (4) schedules to show changes in certain accounts, and (5) no formal papers. The purpose of this article is to indicate the present state of development of the working sheet and the "T" account solution methods and to illustrate a new working sheet approach which is believed to be superior to other methods. The problem in Exhibit I that is used in this article for illustrative purposes was given on the November 1951, Uniform Certified Public Accountants Examinations Accounting Practice. The primary objective of this article has been to illustrate a simple working sheet plan for the quick solution of source and application of funds problems. The working sheet proposed here is easy for students to learn because it uses straight-forward entries instead of reversing entries. Furthermore, it enables a person to work a funds statement problem in less time than is required by conventional working sheets, "T" accounts, or schedules. It is vastly superior to the haphazard plan that makes use of marginal notes on the problem sheet itself without the use of formal working papers.